Analysis of physical training influence on the technical execution of the dismounts off the uneven bars - V. Potop; M. Cretu (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: highlighting of physical training dynamics and its influence on the biomechanical characteristics of the dismounts off uneven bars executed by junior gymnasts aged 12 to 15 years. Material: a number of 8 gymnasts aged 12 to 15 participated in this research. They performed 12 dismounts off the uneven bars during the Women's Artistic Gymnastics Junior National Championships in the all-around event and apparatus finals. The technical execution of the uneven bars dismounts was assessed by means of Physics ToolKit and Kinovea programs in accordance with the method of movement postural orientation, monitoring the key elements of sports technique. Seven tests of motricity were used in this study: 3 tests for strength-speed of lower limbs and arms, 3 tests for strength of the abdominal, back and complex muscles and 1 test of specific endurance. Results: We highlighted the level of specific physical training of junior gymnasts aged 12-15 years; the kinematic and dynamic analysis of the key elements of sports technique in terms of trajectories of body segments, angular speeds and moment of force in the dismounts off uneven bars; also, the dynamics of sports performances achieved in competitions. Conclusions: regarding the correlation of the physical training indicators with the indicators of the kinematic and dynamic characteristics of the dismounts off uneven bars consistent with the results achieved in competition, we revealed strong connections between indicators at P<0.05 and P<0.01 which confirms the influence of the physical training on the technical execution of the dismounts off uneven bars executed by junior gymnasts.